Adherence to nutritional recommendations in vending machines at secondary schools in Madrid (Spain), 2014-2015 - Doris Xiomara Monroy-Parada; María Luisa Jácome-González; María Ángeles Moya-Geromini; Fernando Rodríguez-Artalejo; Miguel Ángel Royo-Bordonada (Elsevier, 2018)
Objective: To describe the nutritional content of products offered in food and drink vending machines at secondary schools in the Madrid Autonomous Community (Spain), and to evaluate these items' adherence to the nutritional recommendations of the National Health System Consensus Document on School Food. Methods: Cross-sectional study of a sample of 330 secondary schools in Madrid across the period 2014-2015. Secondary school vending machines were identified by telephone interview. The products offered in a representative sample of six machines were identified by inspection in situ, and their nutritional composition was obtained from the labelling. Results: A total of 94.5% of the 55 products on offer failed to comply with at least one nutritional criterion of the Consensus Document on School Food. The recommendation relating to sugar content registered the highest level of non-compliance, with 52.7% of products, followed by the recommendations relating to energy (47.3%) and fats (45.5%). The mean number of unmet criteria was 2.2, with this figure being higher in foods than in drinks (2.8 versus 1; p <0.01). Conclusion: Almost all the products on display in secondary school vending machines in Madrid were in breach of the Consensus Document on School Food, mainly due to an excess of calories, sugars and fats. Compulsory nutritional criteria and a procedure for monitoring adherence should be established, specifying those responsible for performing this task and the corrective measures to be applied in the event of non-compliance. Resumen: Objetivo: Describir el contenido nutricional de los productos ofertados en las máquinas expendedoras de alimentos y bebidas de los centros de educación secundaria de la Comunidad de Madrid (España), y evaluar su adherencia a las recomendaciones nutricionales del Documento de Consenso del Sistema Nacional de Salud sobre la Alimentación en los Centros Educativos. Métodos: Estudio transversal sobre una muestra de 330 centros de educación secundaria de la Comunidad de Madrid durante 2014-2015. Las máquinas expendedoras se identificaron mediante entrevista telefónica. Los productos ofertados en una muestra representativa de seis máquinas se identificaron mediante inspección in situ, y su composición nutricional se obtuvo del etiquetado. Resultados: El 94,5% de los 55 productos ofertados incumplía al menos uno de los criterios nutricionales del documento de consenso. La recomendación relativa al contenido de azúcares presentó el mayor grado de incumplimiento, con un 52,7% de los productos, seguida de las relativas a la energía (47,3%) y las grasas (45,5%). La media de criterios incumplidos fue de 2,2, siendo superior en los alimentos que en las bebidas (2,8 frente a 1; p <0,01). Conclusión: Casi todos los productos de las máquinas expendedoras de los centros de educación secundaria de la Comunidad de Madrid incumplen el Documento de Consenso, principalmente por exceso de calorías, azúcares y grasas. Se recomienda establecer criterios nutricionales de obligado cumplimiento y un procedimiento para monitorizar la adherencia a los mismos, con identificación de sus responsables y previsión de medidas correctoras en caso de incumplimiento. Keywords: Childhood obesity, Vending machines, Secondary education, Madrid, Palabras clave: Obesidad infantil, Máquinas expendedoras, Enseñanza secundaria, Madrid